في تعليم علم اللغة النفسي (MULTILITERACY TEACHING) التعليم المتعدد في القراءة والإنتاجات اللغوية - Nur Diana Arifah (OKARA: Jurnal Bahasa dan Sastra, 2018)
Teaching and learning process in psycholinguistic class was conducted for ages, it was found some problems. The first is students’ difficulty in understanding the new term in psycholinguistic. The second, it was the first time for them learning psycholinguistic because they never studied it before. The third is they felt difficult in presenting the material because lack of motivation in reading it. Based the condition above, the researcher was interested in doing the research on implementing multi literacy in teaching and learning process of psycholinguistic class. Research methodology in this research is using descriptive qualitative research that used to research student of the 3rd semester of Arabic Education Department IAIN Madura. The results of the research are 1) multi literacy learning model is able to get students used to analyze the material with critical reading, 2) conveys reading comprehension by summarizing material both individual and groups, 3) produce reading results by speaking in brainstorming, 4) directing them to scientific demonstration of creativity in designing instructional media by utilizing books and internet or other sources of learning.